Spectral Trends across the Rings and Inner Moons of Uranus and Neptune from JWST NIRCam Images - M. M. Hedman; I. de Pater; R. J. Cartwright; M. El Moutamid; R. DeColibus; M. R. Showalter; M. S. Tiscareno; N. Rowe-Gurney; M. T. Roman; L. N. Fletcher; H. B. Hammel (The Planetary Science Journal)
JWST NIRCam images provide low-resolution spectra of the rings and inner moons orbiting Uranus and Neptune. These data reveal systematic variations in spectral parameters like the strength of the strong OH absorption band around 3 μ m and the spectral slopes at continuum wavelengths. Neptune’s rings show an extremely weak 3 μ m band, which is likely due to the small particle sizes in these dusty rings. Neptune’s small inner moons also have weaker 3 μ m bands and redder continua than Uranus’ small inner moons, indicating that Neptune’s moons have a lower water-ice fraction. There are also clear spectral trends across the inner Uranian system. The strength of the 3 μ m band clearly increases with distance from Uranus, with the rings having a noticeably weaker 3 μ m band than most of the small inner moons, which have a weaker 3 μ m band than the larger moons like Miranda. While the rings and most of the small moons have neutral spectra between 1.4 and 2.1 μ m, the outermost small moon Mab exhibits a blue spectral slope comparable to Miranda, indicating that Mab’s surface may also be relatively water ice rich. The next moon interior to Mab, Puck, exhibits a stronger 3 μ m band and bluer continuum slope than any of the moons orbiting interior to it, perhaps indicating that it is being covered by water-ice-rich material derived from Mab via the μ ring. Finally, the small moon Rosalind has a redder spectral slope than its neighbors, possibly due to being coated with material from the dusty ν ring.